ANALISIS PENGARUH HUKUM PERLINDUNGAN KONSUMEN TERHADAP TANGGUNGJAWAB KELALAIAN DAN KESALAHAN PRODUSEN - Nurasiah Panjaitan; Hasbi Febriansyah Sihotang (Al Qadhi, 2023)
The aim of this research is to analyze the impact of consumer protection laws on producer negligence and errors. Consumer protection is an important aspect of law which aims to protect consumer rights and ensure that producers are responsible for the products they produce. Analysis of legal documents, case studies, and literature reviews will be the research methods used to gain an in-depth understanding of legal provisions related to producer responsibility and consumer protection. The focus of this research is the applicable law from a consumer protection perspective and how this law impacts the manufacturer's obligations in the event of product negligence or defects. Research shows that consumer protection laws have a significant impact on manufacturers' liability for product negligence and defects. This legal provision protects consumers from unsafe or defective products and provides a legal basis for consumers to request compensation if losses are caused by manufacturer negligence or defects. This study also identified several challenges in the implementation of consumer protection laws, including obstacles in law enforcement and protection of consumer rights. Therefore, this research provides recommendations for improving or strengthening the consumer protection legal framework to increase its effectiveness in dealing with responsibilities. manufacturer negligence and malpractice.